RELATIONSHIP BETWEEN BENEFITS BARRIERS, AND HEALTH BEHAVIORS TOWARD PREVENTING THE SPREAD OF CORONAVIRUS IN PEOPLE ELDERDY LANKRABUE DISTRICT KAMPHAENGPHET PROVINCE - Budtrachan, Boonlert (Primary Health Care Journal (Northeastern Edition), 2023)
This is Mixed Methods Research aimed to study the relationship between perceived benefits and perceived barriers with behavior to prevent the spread of the corona virus and to create guidelines for behavioral change in preventing corona virus prevention in the elderly, a mixed data collection method was used: 1) Quantitative data were collected through questionnaires among the elderly in Lan Krabue District, Kamphaeng Phet Province, totaling 362 people by simple random sampling. By group chat the main informants are There were 14 elderly people with high and low levels of coronavirus epidemic prevention behaviors. Data were collected from June to July 2022. The data were analyzed using statistics of frequency distribution, percentage, mean, and standard deviation. The relationship was analyzed by Pearson's correlation coefficient, and content analysis. The results showed that elderly people in the area of Lan Krabue District, Kamphaeng Phet Province There is a perception of the benefits of the practice, the overall score was high ( = 4.30, SD = 0.51). Overall was low ( = 1.92, SD = 0.96) and behavior to prevent the spread of the Corona virus. overall was at a high level ( = 4.24, SD = 0.65). and perceived barriers to practice with statistical significance (r = 0.762 and -0.604, p-value < .05). Behavioral change guidelines for the prevention of coronavirus disease prevention among the elderly are recommended methods for cleaning cloth masks. social distancing and strictly implementing DMHT measures. Conclusion: The elderly should be developed to perceive the benefits and perceive the obstacles of the practice. It is an important way to solve the problem of the epidemic area of the corona virus-2019.